Experimental determination of prestressing wire bond and splitting propensity characteristics through tensioned pullout tests - Holste, Joseph Robert (Kansas State University, 2014)
This dissertation describes a testing program to evaluate the bond and splitting propensity characteristics of 5.32-mm-diameter prestressing wires. Prestressing wire reinforcement is used primarily in the production of prestressed concrete railroad ties. Twelve different 5.32-mm-diameter wires were tested in this study in order to measure bonding characteristics of the reinforcement. Establishment of the bond-slip characteristics of these reinforcement at both transfer of prestress (transfer bond) and under flexural loading (flexural bond) is necessary to enable the accurate modeling of these ties using finite elements. Transfer bond and flexure bond of various indent patterns were tested using tensioned pullouts. Specimens of various sizes with single or multiple wires were tested to determine the effects of cover and wire number on bond. Indents were machined on smooth prestressing wires to accurately compare indent geometries. Lateral expansion was tested to determine which wires have higher propensity to cause cracking or splitting. Crossties were instrumented to compare resulting lateral expansion with results found in the laboratory. The results from the testing program showed that the tensioned pullout test was able to be used to predict the transfer length of prisms made with the same reinforcement. The results also showed that the indent geometries were able to be used to predict the splitting of specimens based on the amount of slip the wire had experienced. The testing also showed the importance of concrete cover with the relation to splitting potential.
Keywords: Prestress; Wire; Splitting; Crack; Concrete; Railroad; Civil Engineering (0543)